LPDA-inspired material-geometry joint wide-angle broadband absorption based on metapyramid - Wang, Yanzhao (2024)
The rapid development of metamaterials offers a new avenue to achieve exotic electromagnetic properties, such as perfect absorption for important stealth engineering applications. So far, there are few demonstrations of wide-angle broadband absorption, due to the stringent impedance matching requirement. Here, inspired by the concept of log-periodic dipole antenna (LPDA) for broadband emission, we propose a wide-angle broadband absorption based on both indium tin oxide (ITO) material and judiciously engineered metapyramid geometry. The strip ITO arrays on the sidewalls of metapyramid follow the quasi-LPDA strategy for gradient impedance and expands significantly both angular and spectral operating bandwidth by a cascading of multiple electric and magnetic resonances, as revealed by the rigorous characteristic mode analysis. Our experimental results show that the exotic absorption reaches above 0.9 at 45° tilted incidence for both transverse electric and transverse magnetic polarizations across the band of 8 ∼ 18 GHz. Our strategy circumvents the issues of limited-angle operation, high costs and high weight raised by metal structures, providing a new paradigm toward wide-angle broadband metadevices.